Homilies on the Psalms: Codex Monacensis Graecus 314 - Origenes 185-254 (The fathers of the church, 2020)
Intro -- Contents -- Acknowledgments -- Abbreviations -- Select Bibliography -- Introduction -- The Discovery of CMG 314 -- Preaching -- Grammar -- Principles of Interpretation -- What We Learn from the Homilies -- This Translation -- Homilies on the Psalms: Codex Monacensis Graecus 314 -- Homily 1 on Psalm 15 -- Homily 2 on Psalm 15 -- Homily 1 on Psalm 36 -- Homily 2 on Psalm 36 -- Homily 3 on Psalm 36 -- Homily 4 on Psalm 36 -- Homily 1 on Psalm 67 -- Homily 2 on Psalm 67 -- Homily 1 on Psalm 73 -- Homily 2 on Psalm 73 -- Homily 3 on Psalm 73 -- Homily on Psalm 74 -- Homily on Psalm 75